Calibration of the B/Ca proxy in the planktic foraminifer Orbulina universa to Paleocene seawater conditions. (17th June 2017) - Haynes, Laura L.; Hönisch, Bärbel; Dyez, Kelsey A.; Holland, Kate; Rosenthal, Yair; Fish, Carina R.; Subhas, Adam V.; Rae, James W. B.
Abstract: The B/Ca ratio of planktic foraminiferal calcite, a proxy for the surface ocean carbonate system, displays large negative excursions during the Paleocene‐Eocene Thermal Maximum (PETM, 55.9 Ma), consistent with rapid ocean acidification at that time. However, the B/Ca excursion measured at the PETM exceeds a magnitude that modern pH calibrations can explain. Numerous other controls on the proxy have been suggested, including foraminiferal growth rate and the total concentration of dissolved inorganic carbon (DIC). Here we present new calibrations for B/Ca versus the combined effects of pH and DIC in the symbiont‐bearing planktic foraminifer Orbulina universa, grown in culture solutions with simulated Paleocene seawater elemental composition (high [Ca], low [Mg], and low total boron concentration ([B]T ). We also investigate the isolated effects of low seawater [B]T, high [Ca], reduced symbiont photosynthetic activity, and average shell growth rate on O. universa B/Ca in order to further understand the proxy systematics and to determine other possible influences on the PETM records. We find that average shell growth rate does not appear to determine B/Ca in high calcite saturation experiments. In addition, our "Paleocene" calibration shows higher sensitivity than the modern calibration at low [B(OH)4 − ]/DIC. Given a large DIC pulse at the PETM, this amplification of the B/Ca response can more fully explain the PETM B/Ca excursion. However, further calibrations with other foraminifer species are needed to determine the range of foraminifer species‐specific proxy sensitivities under these conditions for quantitative reconstruction of large carbon cycle perturbations. Key Points: The boron/calcium proxy is calibrated in Orbulina universa for application to ocean acidification during the Paleocene‐Eocene Thermal Maximum Neither seawater [Ca] nor growth rates affect the proxy; instead, it depends on the ratio of seawater borate/dissolved inorganic carbon or borate/bicarbonate Our "Paleocene" calibration can more fully explain the previously measured B/Ca excursion at the Paleocene‐Eocene Thermal Maximum